Best Least Square Solution of Boundary Value Problems Associated with a System of First Order Matrix DifferentialEquation - Swapna, N.; Udaya Kumar, S.; Murty, K.N. (Электронное моделирование, 2015)
The best least square solution of the boundary value problem is constructed via modified QR algorithm and also RQ algorithm. As a result of this work one has a choice of effective methods for finding solutions to two point boundary value problems in the non invertible case. Further these results are exemplified with suitable examples to highlight the modified QR and RQ algorithms.